Epithelial expression of Gata4 and Sox2 regulates specification of the squamous–columnar junction via MAPK/ERK signaling in mice - Nao Sankoda (Nature Portfolio, 2021)
How boundary regions form in the epithelia of tissues, for example, the squamous–columnar junction is unclear. Here, the authors identify the transcription factors Sox2 and Gata4 as specifying the transitional epithelium in the murine squamous–columnar junction region in the stomach epithelia.